Assessment of axial bone rigidity in rats with metabolic diseases using CT-based structural rigidity analysis. Issue 2 (February 2012) - Smith, M. D.; Baldassarri, S.; Anez-Bustillos, L.; Tseng, A.; Entezari, V.; Zurakowski, D.; Snyder, B. D.; Nazarian, A.
Abstract : Objectives: This study aims to assess the correlation of CT-based structural rigidity analysis with mechanically determined axial rigidity in normal and metabolically diseased rat bone. Methods: A total of 30 rats were divided equally into normal, ovariectomized, and partially nephrectomized groups. Cortical and trabecular bone segments from each animal underwent micro-CT to assess their average and minimum axial rigidities using structural rigidity analysis. Following imaging, all specimens were subjected to uniaxial compression and assessment of mechanically-derived axial rigidity. Results: The average structural rigidity-based axial rigidity was well correlated with the average mechanically-derived axial rigidity results (R 2 = 0.74). This correlation improved significantly (p < 0.0001) when the CT-based Structural Rigidity Analysis (CTRA) minimum axial rigidity was correlated to the mechanically-derived minimum axial rigidity results (R 2 = 0.84). Tests of slopes in the mixed model regression analysis indicated a significantly steeper slope for the average axial rigidity compared with the minimum axial rigidity (p = 0.028) and a significant difference in the intercepts (p = 0.022). The CTRA average and minimum axial rigidities were correlated with the mechanically-derived average and minimum axial rigidities using paired t -test analysis (p = 0.37 and p = 0.18, respectively). Conclusions: In summary, the results of this study suggest that structural rigidity analysis of micro-CT data can be used to accurately and quantitatively measure the axial rigidity of bones with metabolic pathologies in an experimental rat model. It appears that minimum axial rigidity is a better model for measuring bone rigidity than average axial rigidity.